2017
DOI: 10.1111/luts.12173
|View full text |Cite
|
Sign up to set email alerts
|

Early Experiences of Contact Laser Vaporization of the Prostate using the 980 nm High Power Diode Laser for Benign Prostatic Hyperplasia

Abstract: Early experience of contact laser vaporization in Japan showed efficacy comparable to transurethral resection of the prostate as a surgical procedure for BPH at 24 weeks. Long-term efficacy of the procedure remains uncertain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 18 publications
6
6
0
1
Order By: Relevance
“…23 Further studies are required to elucidate the adequate output power conditions that minimize postoperative complications while ensuring adequate functional outcomes in CVP.The present study confirmed there is no significant difference in the main safety profile between HPS-PVP and CVP. These perioperative and postoperative complications reported in the present study are in line with the results of previous studies 2,3,6,9,11,18. A total of six patients (5.1%) failed to recover self-urination throughout the followup period after surgery.…”
supporting
confidence: 93%
See 4 more Smart Citations
“…23 Further studies are required to elucidate the adequate output power conditions that minimize postoperative complications while ensuring adequate functional outcomes in CVP.The present study confirmed there is no significant difference in the main safety profile between HPS-PVP and CVP. These perioperative and postoperative complications reported in the present study are in line with the results of previous studies 2,3,6,9,11,18. A total of six patients (5.1%) failed to recover self-urination throughout the followup period after surgery.…”
supporting
confidence: 93%
“…In addition, HPS‐PVP has been confirmed as being safe in high‐risk patients and those with ongoing oral anticoagulation 10 . On the other hand, although there are only a limited number of clinical studies on diode laser vaporization at 980 nm, CVP has provided comparable functional outcomes to TURP or transurethral vaporization with a bipolar system 6,11 . At present, there are only two published prospective studies comparing the different types of laser vaporization for BPH 12,13 .…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations